PERENCANAAN PERLUASAN APRON MENGGUNAKAN PERKERASAN RIGID DI BANDAR UDARA HANG NADIM - BATAM - Ridwan Malik Hanggono; Sukamto; Luky Surachman (Politeknik Penerbangan Indonesia Curug, 2017)
Ridwan Malik Hanggono, ”APRON EXPANSION PLANNING USING RIGID PAVEMENT AT HANG NADIM BATAM AIRPORT”. Indonesian civil aviation institute, Curug-Tangerang. Hang Nadim Batam Airport is the premier first class airport located in Batu Besar, Nongsa, Pulau Batam, Kepulauan Riau and has function to serve transportation services. Those required to provide safe flight and operation services. The high aircraft movement during peak hours in the Hang Nadim Batam Airport it is cause the occur waiting time between the aircraft will land due to less of apron capacity. For the sake of safety it is necessary to support the expansion of the apron to be able to accommodate all aircraft movement during peak hours. Therefore this final project made to explain how to plan the expansion and apron pavement thickness which suitable to the reference of International Civil Aviation Organitation (ICAO) related to the characteristic of the area Mutiara Sis Al-jufri Palu Airport. According to the results of calculation, the dimension of the planned apron is 351,5 x 138,3 m suitable for addition of 8 parking stand and also total area apron pavement thickness is 63 cm. The thickness of concrete slab with concrete quality k-400 is 37,6 cm and 25,4 cm thick subbase for subgrade with CBR 8%.